Sample size considerations in research - Shyam Sivasamy (Endodontology, 2023)
“What should be the sample size for my study?” is a common question in the minds of every research at some point of the research cycle. Answering this question with confident is tough even for a seasoned researcher. Sample size determination, an important aspect of sampling design consideration of a study, is a factor which directly influences the internal and external validity of the study. Unless the sample size is of adequate size, the results of the study cannot be justified. Conducting a study in too small sample size or too large sample size have ethical, scientific, practical, and economic strings attached to it and have detrimental effects in the research outcomes. A myriad of factors including the study design, type of power analysis, sampling technique employed, and acceptable limits of error fixed play a decisive role in estimating the sample size. However, the advent of free to use software and websites for sample size estimation has actually diluted or sometimes complicated the whole process of sample size estimation as important factors or assumptions related to sample size are overlooked. Engaging a professional biostatistician from the very beginning of the research process would be a wise decision while conducting research. This article highlights the important concepts related to sample size estimation with emphasis on factors which influences it.